Novel Gazing : Queer Readings in Fiction - Sedgwick, Eve Kosofsky (Book collections on Project MUSE., 1997)
This is the first collection of queer criticism on the history of the novel. Eve Sedgwick has brought together contributors to navigate this new terrritory through discussions of a wide range of British, French, and American novels--including canonical.